Closeness in Interethnic Friendship (Arabic, Javanese, Tionghoa): A Qualitative Study on Adolescents Living in Surakarta, Central Java, Indonesia - Anggarani, Fadjri Kirana; Helmi, Avin Fadilla; Dewi, Claudia Rosari (Makara Human Behavior Studies in Asia, 2022)
This study aims to describe the formation process of the closeness in interethnic friendship among adolescents living in Surakarta, Central Java, Indonesia. A qualitative study using grounded theory method is employed. Study participants comprised five adolescent girls, aged 16–17 years, with the following interethnic friendships: Javanese–Arabic–Tionghoa, Javanese–Arabic, and Javanese–Tionghoa. Data on the formation process of closeness in interethnic friendship were collected using semi-structured interview referring to the Closeness Interethnic Friendship Guideline for Adolescents. Data were analyzed using initial coding, focused coding, axial coding, and theoretical coding. Results reveal seven composites of closeness in interethnic friendship: disclosure, comfort, compatibility, reappraisal of the characters and other ethnic groups, support, similarity, and togetherness. Closeness led to the continuity of friendship, along with positive emotions, such as excited, comfortable, fun, happy, joyful, content, safe, and proud. This process occurred when the situation supported togetherness as well as, personal quality, experience, and appraisal toward the different ethnic groups, and the shared values understood by all the ethnic groups.